2016
DOI: 10.1111/mve.12193
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitoes of field and forest: the scale of habitat segregation in a diverse mosquito assemblage

Abstract: Knowledge of the distribution of arthropod vectors across a landscape is important in determining the risk for vector-borne disease. This has been well explored for ticks, but not for mosquitoes, despite their importance in the transmission of a variety of pathogens. This study examined the importance of habitat, habitat edges, and the scale at which mosquito abundance and diversity vary in a rural landscape by trapping along transects from grassland areas into forest patches. Significant patterns of vector di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 71 publications
6
43
1
Order By: Relevance
“…However, Mnisi has a constant presence of domestic stock, humans, and diverse birdlife but is located in a dry woodland setting prone to droughts and there were also few mosquito collection events that took place in the area during the study period. Nevertheless, this study supports previous findings suggesting that mosquito diversity is highest in untransformed natural areas such as nature preserves (Marí and Jiménez‐Peydró 2011, Reiskind et al 2017, Cornel et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…However, Mnisi has a constant presence of domestic stock, humans, and diverse birdlife but is located in a dry woodland setting prone to droughts and there were also few mosquito collection events that took place in the area during the study period. Nevertheless, this study supports previous findings suggesting that mosquito diversity is highest in untransformed natural areas such as nature preserves (Marí and Jiménez‐Peydró 2011, Reiskind et al 2017, Cornel et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…albopictus utilizing all three habitats. A similar pattern was observed by Reiskind et al (2017), with host‐seeking mosquitoes sampled along forest‐to‐field ecotones in central North Carolina. In their study, all three species ( Ae.…”
Section: Discussionsupporting
confidence: 85%
“…We used oviposition cups (ovicups) placed at 0 m (representing ground level habitat), 4.5 m (representing mid‐tree level habitat below the canopy level), and 9 m (representing the canopy habitat) (Figure 2). Based on mosquitoes known preferences for shaded environments (Reiskind et al 2017, Scholl and DeFoliart 1977), we expected our collections to be most abundant in the forest habitat, followed by the park, and in least abundance in the campus habitats. We also expected Ae.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely because resting areas and favorable habitats are more prevalent among trees and bushes. Mosquito resting habits indicated by Reiskind et al (2017) found that Cx. pipiens/quinquefasciatus and Ae.…”
Section: Discussionmentioning
confidence: 99%